State feminism in Serbia - institutionalization of feminist policies and practices - Antonijević Zorana (Sociologija, 2016)
The analysis that will be addressed in this paper will be in the outline of understanding the relationship between gender and politics as a dynamic and variable impact of the women’s movement on public policy and their institutionalization. Within the theoretical framework of „state feminism“, I will try to give a critical review of the impact and results of the gender equality mechanisms (women’s policy agencies), especially in relation to the policies and practices of the feminist movement in Serbia. My analysis will be primarily based on the theoretical bases derived from the research project on state feminism (2010) conducted by Dorothy E. McBride and Amy G. Mazur for more than thirty years. Also, some academic work dealing with state feminism concept will be examined trough case studies from the Western Balkans countries (Kesić, 2007,Špehar, 2007, 2012, 2014). Examples from the level of the European Union will be also taken into account (Squires 2007; Kantola and Outshoorn, 2007; Kantola and Dahl 2005; Kantola and Squires, 2012). Also, “state feminism” is examined within the framework of the semi-periphery and policy creation in the process of transition and European Union accession.